Development of Natural Materials Gondorukem with Petroleum Ether, Anchor with Water as Fossil Conservation Materials - Rizky Anindhita; Kun Harismah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Fossil conservation is one form of efforts to preserve fossils through the maintenance andpreservation of fossils. The fossil conservation method commonly used by the SangiranEarly Man Site Preservation Center is the rock conservation method. If a fossil is foundthat is broken or cracked, it is necessary to attach it using an epoxy resin type adhesive.In this study, the experiment that will be carried out aims to provide an alternativeadhesive material from natural materials used for joining fossils and to compare theeffectiveness of natural adhesives with existing adhesives, namely epoxy resin. Naturalmaterials Anchor and Gondorukem (Resina colophonium) have been used as conservationmaterials in Sangiran. Petroleum has never been processed into a conservative solvent forfossil conservation. Therefore, this study chose a petroleum solution to be used as a solventfor the conversion material used to conserve fossils. The way to make adhesive fromnatural materials using petroleum solution is to grind the natural ingredients into powder,which is then dissolved in petroleum solvent before being applied to fossils.